Operational performance and costs of semimecanized thin to waste in Pinus taeda L. - Bonazza M. (2020)
© 2020 University of Sao Paolo. All rights reserved.This study aimed to evaluate and determine performance indicators, production costs and hanged tree percentage for four pre-commercial thinning prescriptions in 5-years-old Pinus taeda stands. The treatments studied were: selective thinning from below with 20% removal of trees (DLB) and selective thinning from above with 20%, 30% and 35% removal of trees (DLA, DMA and DPA, respectively). Randomized blocks experimental design with three replicates of 700 m2 for each treatment was used and a forest inventory was performed to evaluate the blocking effect and stands dendrometric characterization. Operation performance in each treatment was evaluated by elemental level time studies, later, production costs was determined. DLA presented highest productivity and lowest production cost (158.01 R ha-1), followed by DLB (167.30 R ha-1), DMA (224.56 R ha-1) and DPA 260.72 R ha-1), respectively. Tree diameter decreasing led to increased productivity and reduced production costs in all treatments. Hanged tree percentage was higher in treatments with fewer treesremoved per unit area. We concluded that the operation performance and costs were dependent of the treatments and trees diameters, and caution should be taken in operation execution with lower thinning intensities due to the occurrence of higher hanged tree percentages.